DISTRIBUTION OF FOUR-HORNED ANTELOPE (Tetracerus quadricornis) AT RANGAYYANADURGA WILDLIFE SANCTUARY, KARNATAKA, SOUTHERN INDIA - ASHA, B. S.; KUMARA, VIJAYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The pattern of distribution, probability and abundance of the Four-horned antelope (Tetracerus quadricornis) was studied at Rangayyanadurga Wildlife Sanctuary situated in Jagaluru taluk, Davanagere district, Karnataka the study area is said to be a unique refuge for Four-horned antelope one of the smallest Asian bovids, found only in India and Nepal. The study aimed to detect probability, by block count, line, and road transect method to analyze the qualitative distribution of map and abundance of four-horned antelope at Rangayyanadurga Wildlife Sanctuary. The species were found in all three beats of the Sanctuary; both direct and indirect counts were used to plot the distribution map. During the systematic surveys, a total number of 128 direct/indirect signs, 25 individuals in 22 sightings, and 33 defecation sights were reported. The estimated detection probability of the species lies between 0.657±0.004 and the mean group size 1.13/km by direct sighting in transects. According to the result, this species is solitary or semi-solitary by distributing the presence range from 1-to 2 individuals. However, the habitat preference was high in a thorny shrub (~ 45.45 % of observations) as compared to (~27.27% sightings) grassland, dry deciduous (~18.18% of sightings), and agricultural land (~9.09 % of sightings). The area has been found at the edge of its ecological range in a Rangayyanadurga Wildlife Sanctuary. The research emphasizes the primarily prepared distribution map of the FHA by using Arc-GIS 10.3 in the sanctuary for habitat management and conservation.